USING MULTIPLE TEXTS TO TEACH CRITICAL READING SKILLS TO LINGUISTICALLY DIVERSE STUDENTS - Thomas, Kaemanje; Choi, Minkyung (Indonesian EFL Journal, 2019)
Mastery of developmental reading courses offers both an opportunity for academic enrichment and a barrier to college completion. We examine what it means to use multiple texts in college developmental reading courses, the benefits of using them, and considerations that instructors may employ in their instructions. A review of the literature indicates Linguistically Diverse students (LDs) often lack the required critical thinking skills needed to tackle the rigor and demand of their college level courses. We conducted a study to tests whether using multiple texts improved LDs critical reading skills.Â  Participants of 30 undergraduate students taking RDL 500 course were analyzed using pre and posttest results. Findings indicated that integrated use of multiple texts is a practical teaching approach for LDs improved their critical reading skills and their navigation of unfamiliar texts. This implies the use of the one size-fits-all approach may not be an effective pedagogical practice by instructors who teach the LD student.Keywords:Â community college; critical literacy; cultural capital; developmental reading; language minority students; linguistically diverse students; multiple texts; sociocultural literacy.